Predation by mammalian carnivores on nocturnal primates: is the lack of evidence support for the effectiveness of nocturnality as an antipredator strategy? - Burnham, D; Bearder, S; Cheyne, S; Dunbar, R; Macdonald, D (2012)
The apparent paucity of accounts of predation, particularly by felids, on nocturnal primates is confirmed by a quasi-systematic review of 1,939 publications which revealed just 1 case of a felid eating a nocturnal primate. This instance was amongst only 51 direct reports of predation by vertebrates on nocturnal primates (90% were on Madagascar, where 56% of approx. 110 nocturnal primate species occur), of which 41% were by birds of prey. These findings prompt discussion of two possibilities: (a) nocturnality is, in part, an effective antipredator adaptation, and (b) knowledge of nocturnal primates is so biased by their elusiveness and, for predation, underreporting (e.g. inadequate mechanisms to publish opportunistic observations) that understanding of their biology urgently necessitates both the collation of field observations and innovative research. Interspecific comparisons facilitate deductions about the role of predation in the evolution of primate nocturnality and associated traits, but intraspecific comparisons of changing activity rhythms in response to different levels of predation risk offer the most compelling insights into the functional significance of these adaptations.